Using Data Communication to Give Ease in Hotel Room Services - Rudi Tjiptadi (Bina Nusantara University, 2011)
Gaining extra comfort in a trip is an important factor. Staying in a hotel needs food, laundry, and other activities that can make guests comfortable. The guesses’ requests are usually ordered to the Room Service. Sometimes problems occur in serving the guests’ requests due to human error, such as overdue orders, misunderstandings, etc. Computers are used to prevent those problems by typing requests directly from a computer in the room. The method is done by collecting data from the direct interview at a hotel related to guests’ requests, analyzing the current system, doing literature study, creating a Room Service system draft, as well as implementing the new system in a form of prototype. A Room Service system prototype is created with the abilities to order food, drinks, laundry and ironing. This prototype designed meets the guests’ satisfaction towards the hotel room services.